Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2004
DOI: 10.1145/985692.985729
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interruption style on end-user debugging

Abstract: Although researchers have begun to explicitly support enduser programmers' debugging by providing information to help them find bugs, there is little research addressing the proper mechanism to alert the user to this information. The choice of alerting mechanism can be important, because as previous research has shown, different interruption styles have different potential advantages and disadvantages. To explore impacts of interruptions in the end-user debugging domain, this paper describes an empirical compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…Robertson et al [7] studied the effects of immediate-style interruptions and negotiated-style interruptions on users debugging spreadsheet errors. Immediate-style interruptions are interruptions that require user action.…”
Section: Interuption Cost and Effectsmentioning
confidence: 99%
“…Robertson et al [7] studied the effects of immediate-style interruptions and negotiated-style interruptions on users debugging spreadsheet errors. Immediate-style interruptions are interruptions that require user action.…”
Section: Interuption Cost and Effectsmentioning
confidence: 99%
“…A number of studies have shown that, in terms of supporting human performance of all kinds, negotiation-based methods in which users are alerted that there is a notification, but are able to control whether or when the full content of the notification is displayed, are preferable to simpler models in which the full notification is delivered immediately [19,20,24]. Czerwinski et al also found that delivering a preinterruption warning prior to the delivery of the content of the interruption can also have a significant positive effect on performance [8].…”
Section: Task Interruption Studiesmentioning
confidence: 99%
“…A number of studies have shown that, in terms of supporting human performance of all kinds, negotiation-based methods in which users are alerted that there is a notification, but are able to control whether or when the full content of the notification is displayed, are preferable to simpler models in which the full notification is delivered immediately [20,21,24]. Czerwinski et al also found that delivering a preinterruption warning prior to the delivery of the content of the interruption can also have a significant positive effect on performance [9].…”
Section: Task Interruption Studiesmentioning
confidence: 99%